Making Air Quality Data Meaningful: Coupling Objective Measurement with Subjective Experience through Narration - Liu, Szu-Yu (Cyn); Cranshaw, Justin; Roseway, Asta (DIS2020, 2020)
Air pollution causes several million deaths every year. Increasing public awareness through the deployment of devices that sense air quality may be a promising step in addressing the problem; however, these wholly objective device measurements may not capture the nuanced and lived experiences people have with the air, which are often colored by perceptions, histories, imaginations, and the sociopolitical context in which people live. The gap between objective environmental realities and individuals’ subjective experiences of the environment may make it difficult to form meaning from data, hindering the positive policy outcomes that they are intended to produce. To bridge this gap, we conducted a two-phase design fieldwork to obtain an empirical understanding of the rich contours of experiences people have with the air and outline design strategies in making air quality data meaningful.